Health Rights of Refugees, Immigrants and Asylum Seeker - Parisa Yaghoub-Pour; Hosein Dadashzadeh Asl (Jurnal Cita Hukum, 2021)
It has been widely documented that refugees are one of the most vulnerable layers of society to health problems due to poor access to social services, as well as difficulties in housing and nutrition, poor living conditions, and abuse. The health services provided to IDPs are often inadequate and appropriate. Refugees and immigrants have difficulty accessing health care services, medicines, counselling, diagnosis, treatment and rehabilitation services almost all over the world. Today, inequality, regional struggles, and global shifts strongly reflect the ongoing problems of refugees and migrants and their future escalation. This study uses a qualitative research method with a literature approach. The results of the study stated that the settlement of matters regarding their stay, nutrition, accommodation and health services must be prepared in advance, and especially human rights must be respected. In this regard, the actions of governments, civil society organizations and universities at the regional and global levels will contribute to a better future of immigration.Keywords: Refugees and Immigrants; International Immigration; Health Law; Health problems; Health services; Convention Regarding the Status of Refugees Hak Kesehatan Pengungsi, Imigran dan Pencari Suaka AbstrakTelah banyak didokumentasikan bahwa pengungsi adalah salah satu lapisan masyarakat yang paling rentan terhadap masalah kesehatan karena buruknya mendapat layanan sosial, selain karena kesulitan dalam perumahan dan gizi, kondisi hidup yang buruk, dan adanya pelecehan. Pelayanan kesehatan yang diberikan kepada pengungsi seringkali tidak cukup dan layak. Pengungsi dan imigran mengalami kesulitan mengakses layanan perawatan kesehatan, obat-obatan, konseling, diagnosis, pengobatan dan layanan rehabilitasi hampir terjadi di seluruh dunia. Saat ini, ketidaksetaraan, perjuangan regional, dan pergeseran global sangat mencerminkan masalah pengungsi dan migran yang terus berlanjut dan eskalasi mereka di masa depan. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan literatur. Hasil penelitian menyatakan bahwa penyelesaian urusan tentang masa tinggal mereka, nutrisi, akomodasi dan layanan kesehatan harus disiapkan terlebih dahulu, dan terutama hak asasi manusia harus dihormati. Dalam hal ini, tindakan pemerintah, organisasi masyarakat sipil dan universitas di tingkat regional dan global akan berkontribusi pada masa depan imigrasi yang lebih baik.Kata Kunci: Pengungsi dan Imigran; Imigrasi Internasional; Hukum Kesehatan; Masalah kesehatan; Pelayanan kesehatan; Konvensi Terkait Status Pengungsi  Права на здоровье беженцев, иммигрантов и просителей убежища АннотацияШироко задокументировано, что беженцы являются одним из наиболее уязвимых слоев общества с точки зрения проблем со здоровьем из-за плохого доступа к социальным услугам, а также трудностей с жильем и питанием, плохих условий жизни и жестокого обращения. Медицинские услуги, предоставляемые беженцам, часто неадекватны и не соответствуют требованиям. Беженцы и иммигранты почти во всем мире испытывают трудности с доступом к услугам здравоохранения, лекарствам, консультациям, диагностике, лечению и реабилитации. Сегодня неравенство, региональная борьба и глобальные сдвиги во многом отражают текущие проблемы беженцев и мигрантов и их будущую эскалацию. В этом исследовании используется качественный метод исследования с литературным подходом. Результаты исследования показали, что решение вопросов, касающихся их пребывания, питания, проживания и медицинского обслуживания, должно быть подготовлено заранее, и особенно должны соблюдаться права человека. В этом отношении действия правительств, организаций гражданского общества и университетов на региональном и глобальном уровнях будут способствовать лучшему будущему иммиграции.Ключевые Слова: Беженцы и иммигранты; международная иммиграция; закон о здоровье; проблемы со здоровьем; медицинские услуги; конвенция о статусе беженцев